PENINGKATAN KAPASITAS UMKM RAMUAN TRADISIONAL IBU NIFAS KHAS MENTOK MELALUI EDUKASI DAN PENDAMPINGAN - Muhamad Seto Sudirman; Eva Dewi R Purba; Adhi Surya (LPPM ITB AAS Indonesia Surakarta, 2026)
Traditional herbal-based Micro, Small, and Medium Enterprises (MSMEs) have significant potential to preserve local wisdom while improving community welfare. However, the development of traditional postpartum herbal products in Mentok is still constrained by limited public understanding of product legality, packaging, and business management. This community service program aimed to improve community knowledge and skills in developing traditional postpartum herbal products through educational activities, MSME development assistance, and product legalization support. The program was conducted in Tanjung Village, Mentok District, West Bangka Regency, involving local community members and women's organizations (PKK). The implementation employed educational sessions, workshops, hands-on demonstrations, mentoring, and evaluation using pretests and posttests. The results indicated high participant engagement throughout the program. Prior to the intervention, approximately 60% of participants had utilized medicinal plants, while 70% were familiar with the concept of MSMEs; however, their understanding of product legality and packaging remained limited. The program successfully improved participants' knowledge and practical skills, produced five varieties of traditional postpartum herbal products, increased community utilization of traditional herbal remedies, and encouraged the establishment of community-based MSMEs. This program demonstrates an effective community empowerment model for promoting sustainable development of local herbal products.